The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1097/prs.0000000000010354
|View full text |Cite
|
Sign up to set email alerts
|

“Outcomes of the Goldilocks technique in High-risk Breast Reconstruction Patients.”

Abstract: mong the variety of techniques used for breast reconstruction following skin-sparing mastectomy for patients with breast cancer, a few are ideal for patients at high risk of complications. [1][2][3] The original Goldilocks technique, as described by Richardson and Ma in 2012, sought to provide a safe and efficacious alternative for these patients. By folding and shaping mastectomy skin flaps into a breast mound without implants or tissue from other areas of the body, this technique avoids complications traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…These inferior dermal flaps and the mastectomy skin flaps provide a substrate for future serial fat grafting to further augment the reconstruction to create the breast mound. The Goldilocks technique offers shorter operating time, shorter recovery, greater cost-effectiveness, and requires no additional donor site ( 15 ). In this manner, this technique minimizes the complications of both implant- based and abdominally based autologous reconstruction, however may still be used in the setting of implant or autologous reconstruction.…”
Section: Managing the Skin Flapmentioning
confidence: 99%
See 2 more Smart Citations
“…These inferior dermal flaps and the mastectomy skin flaps provide a substrate for future serial fat grafting to further augment the reconstruction to create the breast mound. The Goldilocks technique offers shorter operating time, shorter recovery, greater cost-effectiveness, and requires no additional donor site ( 15 ). In this manner, this technique minimizes the complications of both implant- based and abdominally based autologous reconstruction, however may still be used in the setting of implant or autologous reconstruction.…”
Section: Managing the Skin Flapmentioning
confidence: 99%
“…In this manner, this technique minimizes the complications of both implant- based and abdominally based autologous reconstruction, however may still be used in the setting of implant or autologous reconstruction. When used alone, there is no risk of implant infection, capsular contraction, implant rupture, and decreased risk of fat necrosis, superficial skin loss, and abdominal bulge or hernia ( 15 ). This technique has been shown to be a favorable option for patients with obesity, especially for patients who desire a smaller breast and do not want to undergo a full reconstruction ( 15 , 16 ).…”
Section: Managing the Skin Flapmentioning
confidence: 99%
See 1 more Smart Citation
“…Ghanouni et al show a relatively low rate of complications using the Goldilocks procedure; however, they report that the majority of patients require a second procedure to complete the reconstruction. 4 Asaad et al compared outcomes in 694 two-stage prepectoral and subpectoral breast reconstructions, and found similar rates of complications and patient satisfaction. 5 In their prospective short-term quality-of-life assessment, Sadok et al found that despite increased rates of complications in autologous versus alloplastic breast reconstruction, patient satisfaction was higher…”
mentioning
confidence: 99%
“…W e read with great interest the article "Outcomes of the Goldilocks Technique in High-Risk Breast Reconstruction Patients" by Ghanouni et al 1 The authors describe the technique outcomes, complications, and the likelihood of secondary reconstructive surgery in high-risk patients. There is growing evidence showing that obese patients are two to three times more prone to develop complications after breast reconstruction.…”
mentioning
confidence: 99%